2004
DOI: 10.1124/jpet.104.068189
|View full text |Cite
|
Sign up to set email alerts
|

ITH4012 (Ethyl 5-Amino-6,7,8,9-tetrahydro-2-methyl-4-phenylbenzol[1,8]naphthyridine-3-carboxylate), a Novel Acetylcholinesterase Inhibitor with “Calcium Promotor” and Neuroprotective Properties

Abstract: 7,8,8] naphthyridine-3-carboxylate (ITH4012) is a novel tacrine derivative that can reduce cell death induced by various compounds with different mechanisms of action, such as thapsigargin (reticular stress), H 2 O 2 (free radicals), and veratridine (calcium overload), in bovine chromaffin cell. Cell viability, quantified as lactic dehydrogenase release, was significantly reduced by ITH4012 at concentrations ranging from 0.01 to 3 M. In the human neuroblastoma cell line SH-SY5Y, ITH4012 also reduced amyloid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 27 publications
1
28
0
Order By: Relevance
“…Explanations of the neuroprotective effect observed in these studies included activation of the central cholinergic system [10,12], down-regulation of pro-apoptotic p53 and Bax, stimulation of anti-apoptotic Bcl-2 [5,6,9], or blockage of NMDA receptors [11]. However, no consideration of the role of AChE-S was proposed.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Explanations of the neuroprotective effect observed in these studies included activation of the central cholinergic system [10,12], down-regulation of pro-apoptotic p53 and Bax, stimulation of anti-apoptotic Bcl-2 [5,6,9], or blockage of NMDA receptors [11]. However, no consideration of the role of AChE-S was proposed.…”
Section: Discussionmentioning
confidence: 95%
“…Although the neuroprotective effects of several AChE inhibitors against apoptosis have been reported in vitro, these studies were limited to cell lines or primary cultured cells from the central or peripheral nervous system [5][6][7][8][9][10][11][12]. Explanations of the neuroprotective effect observed in these studies included activation of the central cholinergic system [10,12], down-regulation of pro-apoptotic p53 and Bax, stimulation of anti-apoptotic Bcl-2 [5,6,9], or blockage of NMDA receptors [11].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Orozco et al [39] investigated ITH4012 against a variety of toxic stimuli that may be relevant to the pathophysiology of AD. Their studies indicated that ITH4012 reduced cell death that was induced by thapsigargin (causing reticular stress), H 2 O 2 (through the Propargyl MAO inhibitory moiety free radical mechanism) and veratridine (resulting in Ca 2+ overload) at concentrations in the range of 0.01 -3 µM.…”
Section: Choline/acetylcholineesterase Inhibitors With Additional Cotmentioning
confidence: 99%
“…This compound has been shown in an early study to have AChE inhibitory activity (IC 50 = 0.8 μM) [92]. ITH-4012 was investigated against a variety of toxic stimuli that may be relevant to the pathophysiology of AD [93]. These studies [101,102] indicated that ITH-4012 reduced cell death induced by thapsigargin (causing reticular stress), H 2 O 2 (through the free radical mechanism) and veratridine (resulting in calcium overload), at concentrations ranging from 0.01 μM to 3 μM.…”
Section: Donepezil (Table 4 Aricept®) Is Another Ache Inhibitormentioning
confidence: 99%